(untitled) (Perner’s Contacts, 2015)
The survey analyzes the factors of customer decision-making process by choosing Third-Party Logistics (3PL) in the Czech Republic market. While applying factors by other relevant research studies dealing with the decision-making process of customers in non-European markets, the research examines factors‘ characteristic for the Czech customers. Questionnaires and interviews as qualitative research methods are applied in the research project. Within the research, a new service quality instrument TARRQUAL was developed. The TARRQUAL as service quality measurement is seeked to be applied particularly in logistics business field. The project aims at providing input for empirical research in the field of service quality in container shipping, which is lacking in the Central and East European (CEE) countries.